Studies of a Diastereoselective Electrophilic Fluorination Reaction Employing a Cryo-Flow Reactor - Nakayama, Keiji; Browne, Duncan L.; Baxendale, Ian R.; Ley, Steven V. (Synlett, 2013)
The application of meso-scale flow chemistry in research laboratories continues to increase. Here, we report on the use of a modular cryo-flow device as applied to a diastereoselective fluorination process. The reactor can be incorporated into existing flow chemistry setups to permit continuous processing at low temperatures without recourse to cryogenic consumables.
Keywords: diastereoselective fluorination; flow chemistry; cryo-flow reactor; polymer-supported reagents; chiral auxiliary